Education in Sasak Traditional Society and Local Wisdom related to Environmental Management - Pujilestari, Pujilestari; Suastra, I Wayan; Arnyana, Ida Bagus Putu (Lembaga Penelitian dan Pendidikan Mandala, 2024)
This article discusses the role of education in traditional Sasak society in Lombok which is influenced by local wisdom related to environmental management and cultural preservation. This education involves hereditary practices that focus on ecosystem sustainability, such as the use of traditional medicinal plants which not only function as medicine, but also to maintain environmental balance. Local practices such as the Ngelowong tradition demonstrate an environmentally friendly approach that has long been part of Sasak people's lives. Education based on local wisdom also plays an important role in instilling character values, such as mutual cooperation and respect for nature, in the younger generation. These values are integrated into daily activities, helping to ensure environmental sustainability through the participation of the next generation. This research uses a literature review method, namely examining information published in a certain field of study within a certain time period. Data collection techniques involve searching for journals or books relevant to the research title. The data analysis technique uses Miles and Huberman's theory which includes data reduction, data presentation, and drawing conclusions. With this approach, the Sasak community becomes a model for sustainable environmental management that is relevant for other indigenous communities.